1999
DOI: 10.1902/jop.1999.70.4.438
|View full text |Cite
|
Sign up to set email alerts
|

Retained Free Gingival Graft Rugae: A 9‐Year Case Report

Abstract: In the oral cavity, masticatory mucosa covers the hard palate and gingiva. The epithelium of masticatory mucosa is relatively thick compared to other oral tissues. This results in firmness and immobility necessary to withstand the forces of mastication. In the anterior aspect of the hard palate, long papillae within the lamina propria and thick dense collagenous tissue are found under the transverse ridges or rugae. Though palatal rugae are generally avoided during soft tissue grafting, there are few literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…[2] and Breault et al .,[24] return of the palatal rugae was observed several months postoperatively. Thus, the canine and premolar areas appeared to be the most appropriate donor site for grafting procedures.…”
Section: Discussionmentioning
confidence: 97%
“…[2] and Breault et al .,[24] return of the palatal rugae was observed several months postoperatively. Thus, the canine and premolar areas appeared to be the most appropriate donor site for grafting procedures.…”
Section: Discussionmentioning
confidence: 97%
“…The second bicuspid/first molar area is the site of choice. Selection of the palatal donor site should avoid the rugae areas because they may persist in the grafted tissue for as long as 9 years (10) and consequently compromise aesthetics. Care should also be exercised to avoid the greater palatine foramen area due to potential bleeding and paresthesia.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…In the present study patients did not complain of any significant difference in any of the two groups which is not in conformity with the other studies. 8,10,11 In a review by Tackas 11 lateral pedicle flap was found to be more esthetic than free mucosal graft.…”
Section: Discussionmentioning
confidence: 99%